Exploring Language Learning Theories: The Role of Memory in Acquiring Words and Language Structures - Ginting, Cindy Salsabila; Lubis, Hikmah; Siregar, Muhfita Choiriyah; Lubis, Yani (MUDABBIR Journal Research and Education Studies, 2025)
This qualitative study explores the interplay between prominent language learning theories Behaviorism, Cognitivism, and Constructivism and the role of memory in the acquisition of words and language structures. Employing thematic analysis of 25 core secondary sources, including seminal works and contemporary reviews, the research identifies four overarching themes: (1) Memory as a Repository for Habitual Associations in Behaviorism, (2) Memory as an Information-Processing Tool in Cognitivism, (3) Memory as a Contextual Scaffold in Constructivism, and (4) Integrative Synergies and Divergences Across Theories. Findings reveal memory as a unifying cognitive mechanism that evolves from a passive repository for rote habits to a dynamic processor and scaffold, facilitating lexical retention and structural internalization. Synergies, such as working memory's universal function in real-time processing, bridge theoretical divides, while divergences highlight tensions between mechanistic, innate, and social emphases. Practical implications include hybrid educational strategies for language teaching and cognitive rehabilitation, particularly for learners with memory-related challenges. Limitations, such as reliance on Western-centric sources, suggest avenues for future mixed-methods research. This synthesis advances psycholinguistic understanding, affirming language acquisition as a memory-driven process and promoting integrative approaches for inclusive learning.